The paradox of hikikomori through a transcultural lens - Yoko Nagai; Amy Kartar; Magdalena Pfaff; Hussien Elkholy (BJPsych International)
This article appraises cultural understanding and controversies regarding hikikomori (prolonged social withdrawal), with reference to research over the past 20 years. Initially viewed as a uniquely Japanese phenomenon, hikikomori is now recognised globally, prompting a re-evaluation of its cultural, psychological and socioeconomic demographics. A revision in lifestyle after the COVID-19 pandemic and ongoing technological advancements – particularly the rise of social media, gaming and the internet – have paradoxically both exacerbated isolation and provided new forms of social interaction for young adults who confine themselves at home. This phenomenon underlines the complex interplay between putative individual psychopathology, neurodiversity and broader societal shifts across the globe.